THE USE OF SERVICE DELIVERY ON DEMOCRACY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Service delivery taps into business, marketing, and psychological research andpractices to provide a wealth of knowledge about customer service. It embrace exploringhuman resource staffing practices and service delivery by including proven selectionstrategies for hiring top quality service workers, an analysis of the personality correlates ofservice performance, and a comprehensive review of assessment instruments that predictcustomer service performance. It also provides a framework for customer service as a processand an outcome (Grassel and Zeidler, 2013). In addition, this important resource contains strategies and tactics to improve and manageservice delivery and offers illustrative case examples of how organizations have successfullyimproved and managed customer service. Examples are the use of websites or calls bycustomers to draw the attention of ways to improve services (Skrabeck and Quentin, 2013).